2017
DOI: 10.1159/000475776
|View full text |Cite
|
Sign up to set email alerts
|

An Ecological Study of the Association between Air Pollution and Hepatocellular Carcinoma Incidence in Texas

Abstract: Introduction: Primary liver cancer is a significant cause of cancer-related death in both the United States and the world at large. Hepatocellular carcinoma comprises 90% of these primary liver cancers and has numerous known etiologies. Evaluation of these identified etiologies and other traditional risk factors cannot explain the high incidence rates of hepatocellular carcinoma in Texas. Texas is home to the second largest petrochemical industry and agricultural industry in the nation; industrial activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 23 publications
0
24
1
Order By: Relevance
“…Cicalese et al [1] improperly draw conclusions regarding suggested cause and effect from the associations described by the data in their study. The authors derive effects from estimates of ambient vinyl chloride monomer (VCM) that describe only associations based on inconsistent data.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Cicalese et al [1] improperly draw conclusions regarding suggested cause and effect from the associations described by the data in their study. The authors derive effects from estimates of ambient vinyl chloride monomer (VCM) that describe only associations based on inconsistent data.…”
mentioning
confidence: 87%
“…Table 1 [1] indicates, for example, that VCM was found to have a statistically significant association with HCC using model 1 for data years 2002 and 2005 but not for data years 1996 and 1999. Model 2 indicated that VCM was associated with HCC for all 4 data years.…”
mentioning
confidence: 99%
“…
Dear Editor, This letter is in response to the article "An ecological study of the association between air pollution and hepatocellular carcinoma incidence in Texas" by Cicalese et al [1], where the authors used nonparametric generalized additive logistic regression and gamma regression models to examine the association between county-level concentrations of air pollutants and hepatocellular carcinoma (HCC) incidence rates, concluding that vinyl chloride is a significant contributor to the incidence of HCC in Texas. We believe that these findings are unsubstantiated and misleading given the severe methodological limitations of the paper that we describe below.

As an ecological study, this study is limited by measuring both exposure and outcome at the population level rather than the individual level.

…”
mentioning
confidence: 99%
“…In response to the comments [1, 2] regarding the article by Cicalese et al, “An Ecological Study of the Association between Air Pollution and Hepatocellular Carcinoma Incidence in Texas” [3], the authors acknowledge minor editorial errors but stand behind the methodology and conclusions of the paper. There appears to be a misunderstanding concerning what these data and results suggest; we aim to clarify these points and respond to critiques that the authors knowingly published results based on limited assumptions.…”
mentioning
confidence: 99%
“…Quoted material is reproduced from either the comments submitted to the editor [1, 2] (numbered) or the published paper [3] (bulleted).…”
mentioning
confidence: 99%